Analysis of Company Tax Compliance Related to Foreign Investment: Case Study in Indonesia - Purwanto, T A; Safitri, M (KnE Social Sciences, 2018)
This research is an application to realize a system that is capable of providing data and information between levels of economic growth and Indonesian export between 2010 and 2015. Data from the system that was created dug deeper to find out the prediction of drug distribution in the future. The system to be built is the system that is able to predict the level of export needs that will happen in time (month/year) that you want based on the data of the time (month/year) using ANFIS system. The ANFIS system will search the best function to predict the export needs in the year 2010. Furthermore, the output is used as the data in 2010. The data is output as the prediction will be matched with actual data, whether the resulting function of ANFIS system has a small error. If so, then the function obtained is optimal. Keywords: time series prediction, neural network, ANFIS